2013
DOI: 10.1016/j.cbi.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of diphenyl diselenide in a mouse model of brain toxicity

Abstract: Interest in organoselenide chemistry and biochemistry has increased in the past three decades, mainly due to their chemical and biological activities. Here, we investigated the protective effect of the organic selenium compound diphenyl diselenide (PhSe)2 (5 μmol/kg), in a mouse model of methylmercury (MeHg)-induced brain toxicity. Our group has previously demonstrated that the oral and repeated administration (21 days) of MeHg (40 mg/L) induced MeHg brain accumulation at toxic concentrations, and a pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 66 publications
3
33
0
1
Order By: Relevance
“…Diphenyl diselenide was proved effective against the toxicity of mercury in rodents, while selenite showed no efficacy. 1,19 It was also found that the influence of selenium was dependent on its dose. 10,36 The detailed information is collected in Tables 3-8.…”
Section: Protective Properties Of Selenium Against Environmental Contmentioning
confidence: 99%
See 3 more Smart Citations
“…Diphenyl diselenide was proved effective against the toxicity of mercury in rodents, while selenite showed no efficacy. 1,19 It was also found that the influence of selenium was dependent on its dose. 10,36 The detailed information is collected in Tables 3-8.…”
Section: Protective Properties Of Selenium Against Environmental Contmentioning
confidence: 99%
“…21 The research more and more often includes selenoorganic compounds -either naturally occurring forms or newly synthesized substances, e.g., selenomethionine, naphthalimide-based selenocyanates, 2-(5-selenocyanatopentyl)-benzo[de]isoquinoline-1,3-dione, diphenyl diselenide, selenofuranoside, p-methoxyldiphenyl diselenide, selenocyanates, and diphenylmethyl selenocyanate. [4][5][6]9,16,17,19,20,[22][23][24][25][26] The results regarding the comparison of inorganic and organic compounds are not fully consistent, although the newest studies usually reveal plasma urea and plasma creatinine ↑; kidney vitamin C, GSH, GST, GPx, GR, CAT, δ-ALA-D ↓ p-methoxyl-diphenyl diselenide 50 mg/kg or 100 mg/kg, orally 6 days lower dose: plasma urea (±); plasma creatinine (0); kidney GSH, GST, GPx, GR, δ-ALA-D (±); kidney vitamin C, CAT (+) higher dose: plasma urea and plasma creatinine (±), kidney GSH, GST, GPx, GR, vitamin C, CAT (+) kidney δ-ALA-D (±) none ↓ -decrease; ↑ -increase; (+) -full protection; (±) -partial protection; (0) -lack of protection; GST -glutathione S-transferase; GPx -glutathione peroxidase; CAT -catalase; SOD -superoxide dismutase; GSH -reduced glutathione; TBARS -thiobarbituric acid-reactive substances; GR -glutathione reductase; δ-ALA-D -δ-aminolevulinic dehydratase..…”
Section: Comparison Of the Effect Of Different Selenium Forms On Orgamentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic defects in this selenoprotein are associated with severe health issues. SelP−/−knockout mice display a neurological phenotype with subtle disruption of memory processes and spatial learning [60]. Moreover, other researchers have shown reduction in brain Se levels followed by a decrease in Se-dependent enzyme activity and impaired motor coordination in the same model [52,61,62].…”
Section: Selenoprotein Pmentioning
confidence: 99%